Intensifying agricultural production sustainably: A framework for analysis and decision support - Zurek, Monika; Keenlyside, Paul; Brandt, Katharina (International Food Policy Research Institute, 2015)
Sustainable Intensification (SI) has emerged as one of the key strategies for dealing with the ‘monumental’ challenges facing the global food system. This paper reviews current thinking on SI and proposes a decision support tool to enable decision makers to assess the impacts of policy and technology based interventions on food production, food security, incomes and the environment.